Homogeneous and heterogeneous breast phantoms for UWB imaging - Alshehri, Saleh; Sabira, Khatun; Zaiki, Awang (Association for Computing Machinery, 2011)
This paper presents the fabrication of homogeneous and heterogeneous breast phantoms for experimental breast cancer detection use. The phantoms were developed for UWB imaging technique. The fabrication materials were affordable and the process was minimal. Experiments showed that the use of these phantoms was successful.